A Review of Smart Energy Metering System Projects (Jurnal Elektronika dan Telekomunikasi, 2021)
The rule of thumb dictates that for any country to have a stable and sufficient power supply, there must be at least a thousand Megawatts of electricity for every one million population. However, many developing countries generate far less than the population demand. Despite not generating enough, enormous electrical power loss, energy theft, and unpaid bills are major problems bedeviling the power distribution companies. A fundamental process in the electricity cycle is energy metering from power generation to distribution and consumption. For decades now, manual (or conventional) energy meters are used to estimate every end-user's energy consumption. But there are lots of setbacks to these meters. These meters were unable to solve the problems of power loss and theft, giving necessity to developing a metering system that will serve as a solution to all issues emanating from the consumer end. The past decade saw many developments of such meters, where all are based on the internet of things (IoT) technology. Such meters are called – by the early developers – a smart energy metering system (SEMS), or simply, a Smart Meter. While there have been several reviews on SEMS, most were found to be based on the instant billing capabilities of SEMS, system development, and the wireless communication protocols of the systems. This review focuses on individual components of SEMS with particular attention to the different types and modes of sensors used for other applications. It analyzes various SEMS designs, microcontrollers, sensors, modules, transducers, communication protocols, data storage accuracy, and maximum power capability. Also discussed are the achievements and weaknesses of the designs, some future research challenges, and open issues in the implementation of SEMS.